Evaluating The Viability and Impediments of Structural Design Software (STAAD, MIDAS, And ETABS) In the Cabanatuan City: An In-Depth Analysis - Vernadette Ventura; Ronnel Cesista Fabia; Lorinda E. Pascual; Noel T. Florencondia; Rick Donald Sy Manzon (International Journal of Progressive Research in Science and Engineering, 2024)
The construction industry in Cabanatuan City, much like in many other urban centers, relies heavily on advanced technologies and software tools to meet the demands of modern engineering projects. Among these tools, structural design software such as STAAD, MIDAS, and ETABS play a crucial role in aiding engineers and architects in analyzing and designing complex structures. These software programs offer a range of functionalities, including finite element analysis, structural optimization, and dynamic analysis, which are essential for ensuring the safety, efficiency, and functionality of engineering projects. However, despite the widespread use of these software programs in the construction industry, their viability and effectiveness in meeting the specific engineering requirements of Cabanatuan City have not been thoroughly examined. This research seeks to address this gap by evaluating the suitability of STAAD, MIDAS, and ETABS software in the context of Cabanatuan City's engineering needs.